Disability and child sexual abuse: lessons from survivors' narratives for effective protection, prevention and treatment - Higgins, Martina (Jessica Kingsley Publ., 2010)
Seven disabled people with telling stories -- Narrative and enabling stories of child sexual abuse -- An abusive society? -- The double whammy effect -- Expressions and survival of pain -- Organisational abuse -- Who abuses and why? -- Collective identities -- Narratives of the narrative -- Conclusion : towards a non-abusive society